2005
DOI: 10.1016/j.seizure.2005.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Chronic levetiracetam treatment early in life decreases epileptiform events in young GAERS, but does not prevent the expression of spike and wave discharges during adulthood

Abstract: In this study, chronic LEV administration induced a reduction in epileptiform events in young GAERS. This effect persisted to some extent after treatment cessation (PN 61-PN 64), which might indicate a slowing down of epileptogenic processes. However, at the age of 4 months all animals revealed a similar expression of epileptiform discharges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…A significant inhibition of absence- like seizures was observed in LEV-treated SERs compared with controls (59). Recently, similar longlasting antiepileptic effects by LEV have also been observed in genetically absence epilepsy rat from Strasburg (GAERS) (60). Together with our findings, single and repeated administrations of LEV in adult SERs produce unusual long-lasting anti-seizure effects (>4 weeks), which are not considered to be merely due to LEV accumulation in the brain.…”
Section: Antiepileptogenic Effects Of Lev In Serssupporting
confidence: 89%
“…A significant inhibition of absence- like seizures was observed in LEV-treated SERs compared with controls (59). Recently, similar longlasting antiepileptic effects by LEV have also been observed in genetically absence epilepsy rat from Strasburg (GAERS) (60). Together with our findings, single and repeated administrations of LEV in adult SERs produce unusual long-lasting anti-seizure effects (>4 weeks), which are not considered to be merely due to LEV accumulation in the brain.…”
Section: Antiepileptogenic Effects Of Lev In Serssupporting
confidence: 89%
“…However, it has been found that LEV suppressed seizures not only during chronic treatment but also for a long time after its termination. This effect indicating antiepileptogenic activity of LEV has been described in the rat pilocarpine model (Glien et al, 2002), spontaneously epileptic rats (SER) (Yan et al, 2005) and in Genetically Absence Epileptic Rats (GAERS) (Dedeurwaerdere et al, 2005).…”
mentioning
confidence: 64%
“…A potent antiepileptic effect of LEV has been demonstrated in rats kindled with repeated electrical or chemical stimulation (Loscher & Honack, 1993; Klitgaard et al, 1998; Stratton et al, 2003) and in rats genetically prone to convulsive and nonconvulsive seizures (Gower et al, 1995; Bouwman & van Rijn, 2004; Dedeurwaerdere et al, 2005; Ji‐qun et al, 2005). A single injection of LEV induced the maximal antiepileptic effect in about 1 h postinjection.…”
mentioning
confidence: 99%
“…Early treatment of WAG/Rij rats with ethosuximide before the developmental onset of SWD and continued through adulthood was found to suppress seizures and molecular changes usually seen in these rats in adulthood even 3 months after the medication was stopped (Blumenfeld et al, 2008). Early treatment of GAERS for a shorter time period was found to have a similar, but somewhat less strong suppressive effect on SWD epileptogenesis (Dedeurwaerdere et al, 2005). It will be crucial in future studies to test whether early and sustained blockade of SWD in WAG/Rij and GAERS will be sufficient to prevent the observed DTI abnormalities.…”
Section: Discussionmentioning
confidence: 99%